HASIL JAGUNG MANIS (Zea mays var. saccharata) PADA BERBAGAI MACAM PUPUK KANDANG DAN KONSENTRASI EM4 - Fitriana Eka Priyani; Gembong Haryono; Agus Suprapto (Universitas Tidar, 2017)
A research on yield of Sweet Corn (Zea mays var. saccharata) at Various of Manure and Concentration of EM4, was conducted in October – December 2014. The location in District Mungkid, Magelang Regency, with altitude of 350 meters, with latosol soil type and soil acidity 6,0. This research used factorial (2 x 4) experiment with randomized complete block design repeated in three times. The factor is kind of manure : goat manure and chicken manure. The second factor is concentration of EM4 : 0, 5, 10 and 15 ml/l. The results show that increasing of chicken manure increase plant height, cob weight without husk leaves, sugar content, weight of 1.000 dry seeds, dry weight of the shoots and dry weight of roots, but not increase number of leaves. Treatment concentration of EM4 not increase plant height, number of leaves, cob weight without husk leaves, sugar content, weight of 1.000 dry seeds, dry weight of the shoots and dry weight of roots. Increasing concentration of EM4 on goat manure and chicken manure same response by the plant, so it does not improve all parameters were observed.